Quantificação de fusarium verticillioides e supressividade em sistemas de rotação de culturas milho/soja - Porto, Victor Biazzotto Correia (2018)
Crop rotation is widely known for providing many chemical, physical, and biological benefits to the soil. However, many farmers still use the corn monoculture system. This system presents many disadvantages, among which is the survival of pathogens in crop remains. In this context, we aimed to evaluate the survival of Fusarium verticillioides in corn cultural remains and observe the effects of crop rotation on the amount of inoculum from this pathogen. Furthermore, we assessed the impact of crop rotation on the specific suppressiveness of the soil on this pathogen. To do this, we experimented with the 2016/2017 and 2017/2018 harvests using different management systems for corn, soybean, and reposing areas. We quantified the DNA using the real-time PCR technique on samples of corn cultural remains maintained in the field during both harvests. We evaluated the soil suppressiveness through the biological bait methodology where baits are used to recover soil pathogens, in this case, autoclaved corn stalks. We observed that the management systems adopted were efficient in reducing the amount of F. verticillioides DNA in corn cultural remains. The rotation with soybean cultivation promotes an increase in soil supressivity against F. verticillioides. Finally, this study reinforces the importance of crop rotation for the phytosanitary management of diseases.